2022
DOI: 10.3390/jpm12081329
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs as Regulators of Cancer Cell Energy Metabolism

Abstract: To adapt to the tumor environment or to escape chemotherapy, cancer cells rapidly reprogram their metabolism. The hallmark biochemical phenotype of cancer cells is the shift in metabolic reprogramming towards aerobic glycolysis. It was thought that this metabolic shift to glycolysis alone was sufficient for cancer cells to meet their heightened energy and metabolic demands for proliferation and survival. Recent studies, however, show that cancer cells rely on glutamine, lipid, and mitochondrial metabolism for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 220 publications
0
8
0
Order By: Relevance
“…Further important epigenetic gene regulators are a special class of small non-coding RNAs, the miRNAs. Through their dynamic interaction with messenger RNA (mRNA), they are involved in post-translational regulation and play an important role in various biological processes, such as regulating energy metabolism, cell senescence, and apoptosis [ 9 , 10 , 11 ]. For instance, miR-92a has been shown not only to induce cell proliferation in cancer cells but it is involved in apoptosis as well [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further important epigenetic gene regulators are a special class of small non-coding RNAs, the miRNAs. Through their dynamic interaction with messenger RNA (mRNA), they are involved in post-translational regulation and play an important role in various biological processes, such as regulating energy metabolism, cell senescence, and apoptosis [ 9 , 10 , 11 ]. For instance, miR-92a has been shown not only to induce cell proliferation in cancer cells but it is involved in apoptosis as well [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In order to meet their increased energy demands during growth, the glucose metabolism of cancer cells is often accelerated through higher levels of glucose transporters (GLUT). MiR-195, miR-186, and miR-22 directly target the 3′UTRs of several GLUT s and are, therefore, involved in cancer cell energy metabolism [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that fatty acids may also directly contribute to cell proliferation and regulation of cell metabolism. In stark contrast to normal cells, cancer cells exhibit an insatiable demand for energy, membrane constituents, and regulatory factors to facilitate their rapid proliferation (73)(74)(75). Consequently, extensive metabolic reprogramming becomes imperative to sustain this aberrant growth.…”
Section: Discussionmentioning
confidence: 99%
“…Significantly, PRPS1 and RPIA, which are simultaneously elevated in CRC samples, might serve as potential markers for the poorly unknown CRC prognosis. Numerous investigations have shown that 6-Phosphogluconate dehydrogenase (6PGD) is upregulated in many malignancies ( 140 ). 6PGD has been identified as a functioning target of miR-206 and miR-613 in lung tumor cells, and miR-206 and miR-613 are thought to influence 6PGD expression and metabolic switching in cisplatin-resistant ovarian and lung tumor cells ( 141 , 142 ).…”
Section: Mirnas and Pentose Phosphate Pathwaymentioning
confidence: 99%
“…The regulation of PGC-1 by miR-23a may potentially assist the metabolic shift from OXPHOS to anaerobic glycolysis to produce anabolic precursors and support tumor cell growth ( 153 ). Until recently, the importance of the TCA cycle and the control of its activity was underestimated ( 140 ). Pyruvate dehydrogenase protein X component (PDHX) was shown to be a primary target of miR-26a in CRC cells, reported Chen and collaborators ( 154 ), and it is known that miR-26a may modify PDHX expression through specifically targeting the 3′UTR of PDHX.…”
Section: Mirnas and Tca Cyclementioning
confidence: 99%